1982
DOI: 10.2302/kjm.31.71
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the psychotropic effects of caerulein. An open clinical trial in chronic schizophrenic patients.

Abstract: An open clinical trial of caerulein diethylamine, a cholecystokinin analogue, was performed in a total of 58 chronic schizophrenic patients maintained on drugs such as antipsychotic agents without dosage modification. The neuro peptide medication by intramuscular route produced a clinical improvement in 20 cases and was eventually assessed to have been of therapeutic value in 23 cases. Clinical responses to the medication observed in the present series in cluded: subjective changes in mood mostly to become fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The authors drew the conclusion that caerulein had a long-acting antipsychotic effect in chronic schizophrenia. Similar findings have been reported in seven other open studies (Moroji et al 1985;Itoh et al 1982;Kudo, 1983;Albus et al 1984;van Ree et al 1984;Boza & Retondo, 1985;Yamagani et al 1986) which all found some therapeutic benefit when caerulein was administered in dosages ranging from 0-3 to 20/ig per kg bodyweight (see Table 1). In these studies, most of the patients were suffering from chronic schizophrenia, and all were maintained on neuroleptics.…”
Section: Open Studiessupporting
confidence: 85%
See 1 more Smart Citation
“…The authors drew the conclusion that caerulein had a long-acting antipsychotic effect in chronic schizophrenia. Similar findings have been reported in seven other open studies (Moroji et al 1985;Itoh et al 1982;Kudo, 1983;Albus et al 1984;van Ree et al 1984;Boza & Retondo, 1985;Yamagani et al 1986) which all found some therapeutic benefit when caerulein was administered in dosages ranging from 0-3 to 20/ig per kg bodyweight (see Table 1). In these studies, most of the patients were suffering from chronic schizophrenia, and all were maintained on neuroleptics.…”
Section: Open Studiessupporting
confidence: 85%
“…It is commercially available as a drug for testing biliary and pancreatic function; it is reported to produce fewer gastro-intestinal side effects than CCK (Hommer et al 1985). There is a suggestion that it may have more potent CNS effects than CCK-8 (Itoh et al 1982). However, there have been no studies which were specifically designed to compare the efficacy of caerulein and CCK fragments in the treatment of schizophrenia, and a review of the double blind studies in chronic schizophrenia reveal little evidence of efficacy for any of the CCK preparations.…”
Section: Studies Of the Therapeutic Efficacy Of Cck Fragments In Schimentioning
confidence: 99%
“…The evidence suggests no consistent benefit from this regimen. The alpha 2 -agonist clonidine (Freedman et al 1980, 1982), the alpha 1 antagonist prazosin (Hommer et al 1984 b ), GABAergic drugs such as di-n-propyl-acetate (Linnoila et al 1976), baclofen (Simpson et al 1976), gamma-acetylenic acid (Casey et al 1980), gamma-vinyl-GABA (Korsgaard et al 1983; Stahl et al 1985), thyrotropin-releasing hormone (Wilson et al 1973), lysine-8-vasopressin (Korsgaard et al 1981), cholecystokinin (Itoh et al 1982; Nair et al 1982, 1985; Bloom et al 1983; Hommer et al 1984 a ; Mattes et al 1985 a , 1985 b ), beta-endorphin (Gerner et al 1980; Pickar et al 1981) have also been tried. These studies have been reviewed by us elsewhere (Meltzer 1986).…”
Section: Other Approaches To Treatment-resistant Schizophreniamentioning
confidence: 99%
“…Nair and colleagues [1982] reported CCK-33 and CCK-8 [Bloom et al, 19831 were effective in an open trial in neuroleptictreated but resistant schizophrenics. Itoh et al [1982] reported results of an open clinical trial with caerulein (CCK-8 sulfate) and claimed benefit in 23 of 58 neuroleptic-treated chronic schizophrenia patients. The dose of caerulein was 20 or 40 mg and the route was intramuscular.…”
Section: Peptides In the Treatment Of Schizophreniamentioning
confidence: 99%